Education Development in Muhammadiyah and Nahdlatul Ulama from Time to Time - Lathifah Irsyadiyah Husna; Yazida Ichsan; Neysa Salsabila Felasufa Amadea; Wardi Yusro (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
Islamic education in Indonesia has developed from time to time as well as the the development of Muhammadiyah and Nahdhatul Ulama (NU). This article aims to explore the history of the education development of Muhammadiyah and NU from time to time, referring to the historical literature sources using library research methods. The analysis results demonstrate that Muhammadiyah started its movement by focusing on tajdid, or Islamic renewal. In the 19th century, Ahmad Dahlan founded a secondary educational institution, the Muhammadiyah boarding school, to provide religious and other general knowledge. Afterward, when the dualism of the Islamic education system occurred in the 20th century, Muhammadiyah attempted to integrate the secular knowledge brought by the Dutch with religious knowledge. Furthermore, Nahdhatul Ulama, which took part in education, especially Islamic boarding schools, also confirmed that its focus is to educate human resources by aiding the establishment of Islamic boarding schools.